Cerebrospinal Fluid Drainage and Induced Hypertension Improve Spinal Cord Perfusion After Acute Spinal Cord Injury in Pigs. Issue 4 (April 2015) - Martirosyan, Nikolay L.; Kalani, M. Yashar S.; Bichard, William D.; Baaj, Ali A.; Gonzalez, L. Fernando; Preul, Mark C.; Theodore, Nicholas
Abstract : BACKGROUND: Acute spinal cord injury (SCI) is commonly treated by elevating the mean arterial pressure (MAP). Other potential interventions include cerebrospinal fluid drainage (CSFD). OBJECTIVE: To determine the efficacy of aggressive MAP elevation combined with intrathecal pressure (ITP) reduction; our primary objective was to improve spinal cord blood flow (SCBF) after SCI. METHODS: All 15 pigs underwent laminectomy. Study groups included control (n = 3); SCI only (n = 3); SCI combined with MAP elevation (SCI + MAP) (n = 3); SCI combined with CSFD (SCI + CSFD) (n = 3); and SCI combined with both MAP elevation and CSFD (SCI + MAP + CSFD) (n = 3). SCBF was measured with laser Doppler flowmetry. RESULTS: In the SCI group, SCBF decreased by 56% after SCI. MAP elevation after SCI resulted in a 34% decrease in SCBF, whereas CSFD resulted in a 59% decrease in SCBF. The combination of CSFD and MAP elevation resulted in a 24% increase in SCBF. The SCI + MAP group had an average ITP increase of 5.45 mm Hg after MAP elevation 1 hour after SCI and remained at that level throughout the experiment. CONCLUSION: Both MAP elevation alone and CSFD alone led to only short-term improvement of SCBF. The combination of MAP elevation and CSFD significantly and sustainably improved SCBF and spinal cord perfusion pressure. Although laser Doppler flowmetry can provide flow measurements to a tissue depth of only 1.5 mm, these results may represent pattern of blood flow changes in the entire spinal cord after injury. ABBREVIATIONS: CSFD, cerebrospinal fluid drainage ITP, intrathecal pressure LDF, laser Doppler flowmetry MAP, mean arterial pressure SCBF, spinal cord blood flow SCI, spinal cord injury